Beyond the labeled line: variation in visual reference frames from intraparietal cortex to frontal eye fields and the superior colliculus - Caruso, Valeria C. (J Neurophysiol, 2018)
We accurately perceive the visual scene despite moving our eyes ~3 times per second, an ability that requires incorporation of eye position and retinal information. In this study, we assessed how this neural computation unfolds across three interconnected structures: frontal eye fields (FEF), intraparietal cortex (LIP/MIP), and the superior colliculus (SC). Single-unit activity was assessed in head-restrained monkeys performing visually guided saccades from different initial fixations. As previously shown, the receptive fields of most LIP/MIP neurons shifted to novel positions on the retina for each eye position, and these locations were not clearly related to each other in either eye- or head-centered coordinates (defined as hybrid coordinates). In contrast, the receptive fields of most SC neurons were stable in eye-centered coordinates. In FEF, visual signals were intermediate between those patterns: around 60% were eye-centered, whereas the remainder showed changes in receptive field location, boundaries, or responsiveness that rendered the response patterns hybrid or occasionally head-centered. These results suggest that FEF may act as a transitional step in an evolution of coordinates between LIP/MIP and SC. The persistence across cortical areas of mixed representations that do not provide unequivocal location labels in a consistent reference frame has implications for how these representations must be read out. NEW & NOTEWORTHY How we perceive the world as stable using mobile retinas is poorly understood. We compared the stability of visual receptive fields across different fixation positions in three visuomotor regions. Irregular changes in receptive field position were ubiquitous in intraparietal cortex, evident but less common in the frontal eye fields, and negligible in the superior colliculus (SC), where receptive fields shifted reliably across fixations. Only the SC provides a stable labeled-line code for stimuli across saccades.